2022
DOI: 10.3390/neurosci3010008
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress and Brain Plasticity: From Alterations of Brain Morphology to Development of Psychopathology

Abstract: Advances in our understanding of the genetics of mental disorders (MD) have contributed to a better understanding of their pathophysiology. Nonetheless, several questions and doubts remain. Recent research has focused on the role of the environment in developing mental disorders, and the advent of neuroscientific methodologies has opened up new avenues of inquiry. However, the mechanism by which childhood stress affects neurodevelopment via mechanisms, such as gene-environment interactions and epigenetic regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…ELS alters the proliferation, differentiation and survival of neuronal stem cells (NSCs), culminating in disruptions to synaptogenesis, synaptic pruning, and neurotransmission (72,164). Extensive synaptic remodeling also occurs during adolescence, and CAS is known to disrupt synaptic plasticity and myelination with long-term implications for psychology, cognition and behavior (73,279). These neurophysiological differences have largely been attributed to signaling between the HPA axis, GCs and neurogenic factors (e.g., Brain-derived neurotrophic factor and Wnt) (233,234).…”
Section: Mitochondrialmentioning
confidence: 99%
“…ELS alters the proliferation, differentiation and survival of neuronal stem cells (NSCs), culminating in disruptions to synaptogenesis, synaptic pruning, and neurotransmission (72,164). Extensive synaptic remodeling also occurs during adolescence, and CAS is known to disrupt synaptic plasticity and myelination with long-term implications for psychology, cognition and behavior (73,279). These neurophysiological differences have largely been attributed to signaling between the HPA axis, GCs and neurogenic factors (e.g., Brain-derived neurotrophic factor and Wnt) (233,234).…”
Section: Mitochondrialmentioning
confidence: 99%
“…There is considerable evidence in the research suggesting that CA has a complex and non-specific effect on body systems that are associated with multiple health complications on an individual's physiology, behaviors and neural functions [7]. These effects are predisposing factors to chronic diseases such as hypertension, diabetes mellitus and cancer, or can be associated with mental disorders [8], deviant behavior [9] and psychopathology [7]. Previous studies have also suggested that the adverse effects of CA present at any time during the lifespan, even later in adulthood, with long-lasting and permanent effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…'Technostress' and the telomere theory of aging Stress experienced during this crucial period in human development is important to consider from two angles: i) the immediate effects of stress on the still-maturing adolescent brain and its function, and ii) the long-term neurological, physiological, and psychological manifestation of stress experienced in adolescent life. Research data has implicated early-life stressors as significant influencers of neurodevelopment, and in the onset of psychological and physiological morbidities in adulthood (Oginga et al, 2022;Smith & Pollak, 2020). However, studies examining the long-term effects of SM usage on adolescent development are scarce, and no studies have aimed to look at the impacts of SM-induced stress on markers of cellular aging in adolescents.…”
Section: Effects On Sleep Qualitymentioning
confidence: 99%